Covid-19 and border restriction policies: the dilemma of trans-border truck drivers in East Africa - Calvince Omondi Barack; Gerishon Barack Munga (Goodwood Publishing, 2021)
Purpose: The purpose of this paper is to critically assess the challenges that were faced by trans-border truck drivers within the East African Community as a result of the Covid-19 pandemic and its management protocols. Research methodology: While adopting the qualitative research method, this paper has used documents including documented interviews and virtual sources for its data. The data have been analyzed using qualitative content analysis through which themes have been generated for discussions. Results: The EAC member countries should continue to harmonize their health standardization to enable them to enjoy the pursuit and use of OSBP even during pandemics. Limitations: This paper, however, is limited to the long-distance truck drivers and the management of Covid-19 within the East African Community and does not cover other aspects of Coordinated Border Management in the region. Contribution: It provides valuable contributions to the need for harmonization and standardization of operations and health measures within the community as a long-term solution to the challenges of coordinated border management within the community in the face of future pandemics and readiness for the single market regime. Keywords: Truckers, Coordinated border management, Covid-19, East African Community, Relay driving